The History of the Emergence of National Musical Instruments - Sanokul, Do’stov (International Journal of Psychosocial Rehabilitation, 2020)
The article deals with the origins of national musical instruments date back to very distant ages, beginning with the thirteenth century BC, first with percussion instruments, and later on bamboo stems such as trumpets, whistles, rattles and harps, and strings. Furthermore, it expresses the history of stringed percussion instruments, their types and structure.Moreover, valuable thoughts of the encyclopedic scholars such as Abu Nasr Farabi, Ibn Sina, Ibn Zayla, Abu Abdullah Khorezmi, Sayfiddin Urmavi, Abdukadir Maroghi, Abdurahman Jomi, and Dervishali Changi are given in the article.